基于Pro/E的摆线钢球行星传动建模仿真研究 - 王广欣; 朱莉莉; 关天民 (Jixie chuandong)
In order to improve the design quality of end face engagement cycloid steel ball planetary transmission, this paper focuses on the theories and virtue prototypes technique of cycloid steel ball planetary transmission. On the base of deducing meshing theory, by simplifying the parameters and using computer software, the virtue digital prototype of cycloid steel ball planetary transmission is realized. The dynamic motion of the drive is also demonstrated, and the digital prototype provides reference for physical prototype design on this precision transmission. This method can be applied to other similar mechanism design.